Livestock research and development in East and Southern Africa: An innovation systems perspective with special reference to the International Livestock Research Institute - Norman, C.; James, S.; Maija, H. (Intellect, 2007)
The concept of innovation system is used increasingly in current science policy discourse as a metaphor to indicate the need for a much wider perspective on relevant decision-making procedures than has been the case in the past. This paper explores its use from the standpoint of the behaviour of an international agricultural research institute located in Africa and focused on two vector-borne livestock diseases, trypanosomiasis and theileriosis, which form case studies for this paper. The paper argues that adopting an innovation systems perspective could open up new possibilities for research institutes of this type with impacts on both socioeconomic development and scientific quality that are likely to be positive.